Characteristics of Low Reynolds Number Shear-Free Turbulence at an Impermeable Base - W. H. M. Wan Mohtar; A. ElShafie (The Scientific World Journal)
Shear-free turbulence generated from an oscillating grid in a water tank impinging on an impermeable surface at varying Reynolds number 74≤Rel≤570 was studied experimentally, where the Reynolds number is defined based on the root-mean-square (r.m.s) horizontal velocity and the integral length scale. A particular focus was paid to the turbulence characteristics for low Rel<150 to investigate the minimum limit of Rel obeying the profiles of rapid distortion theory. The measurements taken at near base included the r.m.s turbulent velocities, evolution of isotropy, integral length scales, and energy spectra. Statistical analysis of the velocity data showed that the anisotropic turbulence structure follows the theory for flows with Rel≥117. At low Rel<117, however, the turbulence profile deviated from the prediction where no amplification of horizontal velocity components was observed and the vertical velocity components were seen to be constant towards the tank base. Both velocity components sharply decreased towards zero at a distance of ≈1/3 of the integral length scale above the base due to viscous damping. The lower limit where Rel obeys the standard profile was found to be within the range 114≤Rel≤116.